Carboxymethylcellulose derivatives with low hydrophilic properties - Machado, G. O.; Regiani, A. M.; Pawlicka, A. (Polimery, 2022)
New kinds of cellulose derivatives have been obtained by modification of sodium and lithium carboxymethylcellulose (NaCMC and LiCMC, respectively) with commercial octadecylisocyanate (OctI) and hexamethylene-diisocyanate (HDI). The CMC samples were obtained from sugar cane bagasse pulps using sodium hydroxide and anthraquinone mixture. The structural changes of modified samples were observed using infrared spectroscopy (IR), solid state C-13 NMR and thermal analysis (TGA). The samples surfaces were visualized using scanning electron microscopy (SEM) method. The presence of characteristic urethane group absorption bands in the region of 1650-1720 cm(-1) in IR spectra and at 159 ppm in C-13 NMR spectra indicates the formation of the product.